Post Purchase Evaluation: A Behavioral Study - Kurian, Shaji; Sahay, Saurav; Misra, Siddharth (International Journal of Psychosocial Rehabilitation, 2019)
The research aims to investigate the different purchase approaches of consumers and relate them to their post-purchase behavior. And also, to take into consideration what is the variation in post-purchase satisfaction levels. The study uses questionnaire-based investigation using regression analysis through Microsoft Excel. The total number of participating respondents is 170, and they are from various geographical, educational, and professional backgrounds, having bought a wide range of products from mobile phones to real estate, with some of the products bought as recent as 3 months to the products over a year. The findings of the study suggest that emotional dissonance ranks the highest among the post-purchase behavior of the consumer. There is higher emotional dissonance even with decision-making styles that are considered to be using a methodical approach. It has relevant, practical implications in understanding what kind of post-purchase dissonance is present among the consumers and the approach to address it. The empirical evidence adds to the novelty of the paper suggesting that there is presence of consumer dissonance irrespective of the approach of purchase process which is embedded in their emotional style of buying.